Neo-classicism and the other Revivals in 1840 New Zealand: British Domestic Design in Indigenous Materials - Cottrell, William (Architectural History Aotearoa, 2014)
In the first decades of the nineteenth century there was an insatiable enthusiasm for the fashions of previous eras. New research has established that designs for domestic furnishings in America, Australia and New Zealand were concurrent with the latest London and Paris fashions. It may be hard to imagine, with the priorities of convict and missionary life in the Australasian colonies, that influence of some of the greatest English designers was of any importance. Furniture designs by George Hepplewhite (1788), Thomas Sheraton (1794) and Thomas Hope (1807) can be found in New South Wales, while George Smith (1826), Thomas King (1829-35) and John Loudon (1833) can be identified in New Zealand. Elements of current British style trends from thereon can be seen in colonial-made furniture as mainstream fashion. By the 1840s the rare surviving examples made of native timbers are typical of those that could be found in any English home. Evidence does survive and, with interpretation, reveals a consistent influx of modern styles into the new colonies.